Reviewing a Decade of Human–Computer Interaction for Development (HCI4D) Research, as One of Best’s “Grand Challenges” - Van Biljon, Judy; Renaud, Karen (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
The human–computer interaction for development (HCI4D) field emerged at the intersection of the fields of information and communication technology for development (ICT4D) and human–computer interaction (HCI). In 2010, Michael Best nominated HCI4D as one of ICT4D’s “grand challenges”. This HCI4D field is now entering its second decade, and it is important to reflect on the research that has been conducted, and to consider how HCI4D researchers have addressed the challenge that constitutes the raison d’être of HCI4D’s existence. Best provided four guidelines to inform researchers embracing this challenge. This study commences by identifying the primary HCI4D-specific themes, and then carries out a systematic literature review of the HCI4D literature to build a corpus to support the analysis. The corpus is analysed to reflect on how well the field’s practices align with Best’s guidelines. The overall finding is that HCI4D researchers have largely been following Best’s guidelines and that the HCI4D field is demonstrating encouraging signs of emerging maturity.
Keywords: Human–computer interaction for development (HCI4D), information and communication technology for development (ICT4D), human–computer interaction (HCI), guidelines, Michael Best